2008
DOI: 10.1016/j.bbr.2007.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Pup exposure elicits hippocampal cell proliferation in the prairie vole

Abstract: The onset of parental behavior has profound and enduring effects on behavior and neurobiology across a variety of species. In some cases, mere exposure to a foster neonate (and a subsequent parental response) can have similar effects. In the present experiment we exposed adult male and female prairie voles (Microtus ochrogaster) to two foster pups for twenty minutes and quantified cell proliferation in the dentate gyrus of the hippocampus (DG), medial amygdala (MeA) and cortical amygdala (CorA). Prairie voles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 55 publications
5
58
0
Order By: Relevance
“…By 2 weeks after weaning, BrdU labeling does not differ between primiparous and nulliparous females. In another rodent species, the biparental prairie vole, exposure to pups increases BrdU labeling in only those foster parents who did not respond parentally (Ruscio et al, 2008). Combined, these studies indicate that the immediate postpartum decrease in cell proliferation may be necessary for proper maternal behavior, and that the decrease is transient.…”
Section: Changes In Hippocampal Morphologymentioning
confidence: 81%
“…By 2 weeks after weaning, BrdU labeling does not differ between primiparous and nulliparous females. In another rodent species, the biparental prairie vole, exposure to pups increases BrdU labeling in only those foster parents who did not respond parentally (Ruscio et al, 2008). Combined, these studies indicate that the immediate postpartum decrease in cell proliferation may be necessary for proper maternal behavior, and that the decrease is transient.…”
Section: Changes In Hippocampal Morphologymentioning
confidence: 81%
“…Likewise, offspring seem to have a stimulatory effect in virgin females of other rodent species including prairie voles which are biparental and typically display spontaneous parental care when exposed to foster pups. Specifically, Ruscio et al (2008) found that virgin female voles briefly exposed to pups for just 20 min exhibit increased cell proliferation in the DG regardless of whether they behaved parentally. It is important to note however that cell proliferation also increased in response to a control stimulus (i.e.…”
Section: Hippocampal Neurogenesis During Pregnancy and The Postparmentioning
confidence: 96%
“…Thus, fluctuations in other hormones that occur classically during the peripartum period may also play a major role, such as oxytocin and prolactin, which, as mentioned above, have been shown to influence hippocampal neurogenesis (16, 18). Alternatively differential interactions with pups after restraint stress may contribute to the lack of pregnancy/lactation-induced decrease cell proliferation since as pointed out earlier, pup exposure can increase cell proliferation in nulliparous rats (43, 83). In support of this, restraint stress during the first weeks of lactation increased active nursing behavior in dams for the first two hours after stress compared with control dams (82).…”
Section: Animal Models Of Postpartum Depression Based On Stress Exposurementioning
confidence: 93%